Productivity of fodder grasses in the conditions of the Southern Forest Steppe of Ukraine - Antonets, O.; Kocherga, V. (Scientific Progress & Innovations, 2024)
Legume-cereal grasses provide an opportunity to significantly increase the productivity of grasslands. The economic value of plants on natural fodder grounds is determined by their productivity. The bird’s-foot trefoil and crested weat grass have high fodder value. Among the fodder leguminous grasses, the bird’s-foot trefoil is one of the most valuable pasture plants. This plant is a good component of the grass mixture, which ensures the accumulation of root mass. The crested weat grass is a fodder cereal that is also widely used in grass mixtures. Therefore, the urgency of the topic lies in the need to analyze collection samples of the bird’s-foot trefoil and weat grasses for fodder and seed productivity in the conditions of the Southern Forest Steppe of Ukraine. This is important for finding good initial material in analytical selection breeding and solving the problem of seed production. The purpose of the research is to find out the adaptive potential of collection samples of the bird’s-foot trefoil and weat grasses to reveal the productivity of these perspective fodder grasses. The research was conducted at the Ustymivka Experimental Station of Plant growing of the Institute of Plant growing named after V. Ya. Yuriev of NAAS of Ukraine in 2022–2023. The object of the research was 21 collection samples of the bird’s-foot trefoil and 23 collection samples of weat grasses, among which there were crested weat grass and desert weat grass. As a result of the research, an assessment of the collection samples of the bird’s-foot trefoil was carried out according to the yield of green mass, hay and seeds. The best collection samples of UJ0500012, UJ0500100, UJ0500110 and UJ0500112 were selected for the yield of green mass (respectively 2063.80 g/m2, 1798.0 g/m2, 2200.40 g/m2, 2262.30 g/m2) and hay ( respectively 481.80 g/m2, 439.0 g/m2, 557.10 g/m2, 576.10 g/m2). Collection samples of weat grasses were assessed for height before mowing, productivity of green mass after mowings, hay productivity after mowings, and seed productivity. The best sample of crested weat grass UDS00039 was selected out for the height of the plant before mowing (70.6 cm), the yield of green mass (810.1 g/m2) and the yield of hay (272.5 g/m2). The best collection samples of crested weat grass UDS00070, UDS00073, UDS00074 were selected for the yield of green mass (respectively 778 g/m2, 962.8 g/m2, 753.3 g/m2) and hay (respectively 255.2 g/m2, 344.7 g/m2, 270.5 g/m2). The best collection samples of crested weat grass UDS00076 and UDS00081 were selected for plant height before mowing (67.3 cm and 66.9 cm, respectively) and hay yield (259 g/m2 and 256.9 g/m2, respectively). The desert weat grasses sample UDS00018 also performed well in terms of plant height before mowing (65.3 cm) and seed yield (107.5 g/m2). Selected collection samples of the bird’s-foot trefoil and weat grasses are recommended as initial material for analytical selection.